2018
DOI: 10.1186/s12881-018-0698-2
|View full text |Cite
|
Sign up to set email alerts
|

Association between acromegaly and a single nucleotide polymorphism (rs2854744) in the IGFBP3 gene

Abstract: BackgroundIt has been reported that the single nucleotide polymorphism (SNP) rs2854744 at the − 202 locus of insulin-like growth factor binding protein-3 (IGFBP3) is associated with serum levels and a number of malignancies. However, the effect of IGFBP3 gene polymorphism on acromegaly is less clear. Therefore, in the current study, we aimed to investigate whether the −202A/C polymorphism of IGFBP3 constitutes a risk factor for acromegaly.MethodsThe study included 102 acromegalic patients and 143 control subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 25 publications
0
7
0
2
Order By: Relevance
“…Although previous databases included mostly western populations, only East Asians were analyzed in this study 11 , 15 , 16 . In several studies, ethnic differences were significantly associated with clinical manifestations and genetics of GH-secreting pituitary adenoma 17 19 . Furthermore, we analyzed pure GH-secreting pituitary adenomas without GNAS variant rather than general sporadic cases.…”
Section: Discussionmentioning
confidence: 99%
“…Although previous databases included mostly western populations, only East Asians were analyzed in this study 11 , 15 , 16 . In several studies, ethnic differences were significantly associated with clinical manifestations and genetics of GH-secreting pituitary adenoma 17 19 . Furthermore, we analyzed pure GH-secreting pituitary adenomas without GNAS variant rather than general sporadic cases.…”
Section: Discussionmentioning
confidence: 99%
“…Гормонально активні пухлини (аденоми) гіпофіза, клінічними проявами яких є синдром акромегалії, за даними різних авторів, трапляються відносно нечасто і належать до класу орфанних захворювань [1][2][3]. Розвиток пухлини -це складний багатоетапний процес, на який впливають генетичні, епігенетичні фак-тори та чинники довкілля, а також стан центральної нервової системи та мікрооточення пухлини [4][5][6][7]. У більшості випадків моноклональні пухлини гіпофіза, що продукують соматотропний гормон (СТГ), виникають de novo в результаті спорадичних мутацій, а саме генетичних порушень у різних генах, включаючи AIP (aryl hydrocarbon receptor interacting protein), GNAS © 2021.…”
Section: вступunclassified
“…We identi ed 30299 mRNAs in all assemble transcripts. Comparing between the two groups, 780 differential expressed mRNAs were identi ed in which 319 were upregulated and 461 were downregulated signi cantly (P value < 0.05) (Table 1).Then, combining NCBI literature and gene information retrieval, we found that ADGRG1 and IGFBP3 were possibly related NF1with scoliosis [17,19,[22][23][24][25][26][27][28]. Our Further analysis of clinical samples showed that the expressions of ADGRG1 and IGFBP3 both in gene and protein levels were signi cantly decreased in NF1 with scoliosis group than that in the control group(P < 0.001) (Fig.…”
Section: Adgrg1 and Igfbp3 Differential Expressed Between Nf-1 With Smentioning
confidence: 99%